A polyvalent influenza DNA vaccine applied by needle-free intradermal delivery induces cross-reactive humoral and cellular immune responses in pigs. Issue 32 (12th July 2016) - Borggren, Marie; Nielsen, Jens; Karlsson, Ingrid; Dalgaard, Tina S.; Trebbien, Ramona; Williams, James A.; Fomsgaard, Anders
Abstract: Background: Pigs are natural hosts for influenza A viruses, and the infection is widely prevalent in swine herds throughout the world. Current commercial influenza vaccines for pigs induce a narrow immune response and are not very effective against antigenically diverse viruses. To control influenza in pigs, the development of more effective swine influenza vaccines inducing broader cross-protective immune responses is needed. Previously, we have shown that a polyvalent influenza DNA vaccine using vectors containing antibiotic resistance genes induced a broadly protective immune response in pigs and ferrets using intradermal injection followed by electroporation. However, this vaccination approach is not practical in large swine herds, and DNA vaccine vectors containing antibiotic resistance genes are undesirable. Objectives: To investigate the immunogenicity of an optimized version of our preceding polyvalent DNA vaccine, characterized by a next-generation expression vector without antibiotic resistance markers and delivered by a convenient needle-free intradermal application approach. Methods: The humoral and cellular immune responses induced by three different doses of the optimized DNA vaccine were evaluated in groups of five to six pigs. The DNA vaccine consisted of six selected influenza genes of pandemic origin, including internally expressed matrix and nucleoprotein and externally expressed hemagglutinin and neuraminidase. Results: Needle-free vaccination of growing pigs with the optimized DNA vaccine resulted in specific, dose-dependent immunity down to the lowest dose (200 μg DNA/vaccination). Both the antibody-mediated and the recall lymphocyte immune responses demonstrated high reactivity against vaccine-specific strains and cross-reactivity to vaccine-heterologous strains. Conclusion: The results suggest that polyvalent DNA influenza vaccination may provide a strong tool for broad protection against swine influenza strains threatening animal as well as public health. In addition, the needle-free administration technique used for this DNA vaccine will provide an easy and practical approach for the large-scale vaccination of swine.